Breast education for schoolgirls; why, what, when, and how?. Issue 3 (15th November 2017) - Brown, Nicola; Smith, Jenny; Brasher, Amanda; Risius, Debbie; Marczyk, Anna; Wakefield‐Scurr, Joanna
Abstract: Schools are fundamental settings for health education and adolescent females are an important group for promoting positive breast habits. We surveyed 2089 schoolgirls (11‐18 years) to provide evidence for, and guidance on, breast education for schoolgirls. 26% reported negative feelings about their breasts and 87% reported ≥ one breast concern. 72% wanted to know more about breast cancer (69% rating this extremely important). >50% wanted to know more about breast sag and breast pain. Preferred delivery format was age eleven (50%), girls only taught sessions (41%) with female teachers (43%). A need for breast education and delivery preferences was identified.